Latvia - Lerner Publications Company. Geography Dept. (Minneapolis : The Company, 1992)
Discusses the geography, history, ethnography, resources, politics, and future of this Baltic country, annexed by the Soviet Union in 1940 and independent once again in 1991.
Includes index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
7.1
4-6
Keywords: Latvia -- History -- Juvenile literature; Latvia; Latvia